Influences of Pore Distribution of Carbon Electrodes on High-Rate Discharge Capacity and Cell Power in Li/SOCl2 Cell - Mok Chae, Jong; Chung, Kwang-Il; Il Lee, Sang; Soo Kim, Bum (Asian Journal of Chemistry, 2014)
Discharge characteristics of Li/SOCl2 cells are known to be affected by the pore size distributions of carbon electrode. In this study, we investigate effects of the pore distribution of the carbon cathode on the high-rate capacity and cell power. We carry SEM, mercury porosimetry and BET measurements for the characterization of carbon electrodes having different densities or various mixing ratio between acetylene black (AB) and ketjen black (KB). Upon the high-rate discharge characteristics, it is revealed that density effect is more significant than the effect of carbon mixing.